Investigating XBRL diffusion: Toward establishing content validity and pre-test of the questionnaire instrument - Selamat, Mohamad Hisyam; Rawashdeh, Awni (2010)
Studies on extensible business reporting language (XBRL) diffusion are just starting to emerge and most of these studies are exploratory in nature. Progress has been made in developing conceptual models to comprehend the adoption and diffusion of XBRL from the user point of view. However in order to validate the conceptual model of XBRL diffusion, a reliable and valid questionnaire instrument has not yet been developed. Therefore, the purpose of this research in progress article is to achieve the following issues: first, content validity (CV) and second, pre-test (PT) the questionnaire. The aim of this article are: first, to identify factors and their relevant elements that sufficiently cover pertinent dimensions of factors that affects users in the area of XBRL diffusion; second, to identify whether of determine factors that have been identified and pertinent elements adequately cover pertinent dimensions of the factors affecting users in the area of XBRL diffusion; and third, to perform a 'PT 'on resulting questionnaire instrument so as to achieve feedback for further modifications before completing the questionnaire for data collection. Primary elements for each factor were determined from both information system adoption literature and antecedent exploratory studies on XBRL diffusion. Validation of the determined elements that have been identified subsequently is using variations of a quantitative manner to CV. The outcomes resulted from content validation are then offered and discussed thereafter. Finally, the article is performed by focusing the limitations of content validation and putting possible future research direction towards examining XBRL diffusion.